Efficiency of Problem-Based Learning Models to Improve Passing Skills in Basketball Games - Arnaz Anggoro Saputro (Journal of Physical Education and Health Science, 2025)
Passing ability is a fundamental motor skill that plays a crucial role in basketball performance. However, preliminary observations indicated that the passing ability of students at the Leviathan Basketball Club was relatively low. This study aimed to evaluate the effectiveness of problem-based learning in improving students’ basketball passing skills. A quasi-experimental method with a one-group pretest–posttest design was employed. The participants consisted of 21 students who received problem-based learning instruction focused on basketball passing skills over 12 sessions. The data collection instrument was a basketball passing skill test developed based on indicators of fundamental passing techniques and administered before (pretest) and after (posttest) the intervention. The collected data were analyzed using a Paired Sample T-Test with the assistance of SPSS software. The results revealed a statistically significant improvement in students’ passing ability following the implementation of problem-based learning, with a significance value of 0.000 (p < 0.05). It can be concluded that problem-based learning is effective in enhancing basketball passing skills. This study contributes to the understanding of instructional models in physical education and sports, particularly in improving fundamental motor skills. Further research is recommended to explore the application of problem-based learning to other sports skills and broader participant groups.